The Influence of Digital Financial Literacy, QRIS Utilization, and Merchant Discount Rate (MDR) on Financial Management at Mixue Outlets - Seha Ranika; Devyanthi Syarif (Journal of Accounting Inaba, 2026)
The advancement of digital technology has significantly transformed business operations, particularly in payment systems and financial management. Effective financial management is crucial for maintaining business sustainability, improving cash flow control, and supporting strategic decision-making. This study aims to examine the influence of Digital Financial Literacy, QRIS Utilization, and Merchant Discount Rate (MDR) on Financial Management at Mixue Ice Cream & Tea outlets in Greater Bandung. This research employed a quantitative approach using primary data collected through questionnaires distributed to 30 outlet managers. The data were analyzed using multiple linear regression analysis. The results indicate that Digital Financial Literacy has a positive and significant effect on Financial Management (t = 2.306; p = 0.029), while QRIS Utilization has no significant effect (t = 0.525; p = 0.604). In contrast, Merchant Discount Rate (MDR) has a positive and significant effect on Financial Management (t = 8.942; p < 0.001). Furthermore, Digital Financial Literacy, QRIS Utilization, and Merchant Discount Rate simultaneously have a significant effect on Financial Management (F = 73.963; p < 0.001), with an Adjusted R² of 0.883, indicating that 88.3% of the variation in Financial Management is explained by the three independent variables. These findings highlight the importance of strengthening digital financial literacy and effectively managing merchant discount rates to improve financial management practices in franchise-based food and beverage businesses.